A comparative study between endoscope assisted transtympanic pop-in tympanoplasty and permeatal underlay tympanoplasty - Bista, Meera; KC, Toran (Journal of Kathmandu Medical College, 2018)
Background: Otoscopic procedure like tympanoplasty is one of the magic wands that an ear nose throat surgeon possesses to alleviate the suffering of a hearing impaired patient. Endoscopic trans-tympanic pop in technique is an alternative method where tympanic fascial graft is placed medial to tympanic membrane remnant through the perforation without elevation of tympanomeatal flap and angled endoscope is used to assess the ossicular chain.Objective: The study was done to compare the results of endoscope assisted trans-tympanic pop-in tympanoplasty with permeatal underlay tympanoplasty.Methods: The study is a prospective, longitudinal and experimental study conducted in Kathmandu Medical College Teaching Hospital from January 2016 to June 2016. A total of sixty-two patients, thirty-one in study and thirty-one in control group were present. The comparison was made in terms of success rate, decrease in taste sensation and time taken for the procedure. Data analysis was done by SPSS version 20. Categorical data were tested by Fisher Exact test and p-value of